Surgical Excision of Posttraumatic Ossifications at the Proximal Hamstrings in Young Athletes: Technique and Outcomes. (June 2015) - Orava, Sakari; Hetsroni, Iftach; Marom, Niv; Mann, Gideon; Sarimo, Janne; Ben-Zvi, Ofer; Lempainen, Lasse
Background: Proximal hamstring tears can be associated with chronic disability related to the unusual formation of heterotopic ossifications. The role for operative intervention in these circumstances has not been clearly defined. Purpose/Hypothesis: The purpose of this study was to describe the surgical management of young athletes who had chronic disability related to proximal hamstring ossifications after eccentric load injuries. The hypothesis was that after surgical excision of posttraumatic heterotopic ossifications at the proximal hamstrings with concomitant repair of the tendons to the ischium, significant functional improvement with low risk of postoperative complications can be expected at minimum 2-year follow-up. Study Design: Case series; Level of evidence, 4. Methods: The cases of 11 consecutive male athletes who developed chronic disability associated with heterotopic ossifications at the proximal hamstring muscles after sports-related tears were reviewed. During surgery, the ossified mass was meticulously excised, and the tendons were debrided and fixed to the ischium. At minimum 2-year follow-up, self-reported outcome was rated as excellent, good, moderate, or poor . Operative reports and office visits were reviewed. Activity level before the injury and at latest follow-up was graded with the Tegner scale. Results: The median age at injury was 17 years (range, 13-25 years). Sports activities included ice hockey, soccer, track and field athletics, and judo. Mean interval from injury to surgery was 45 months. The smallest ossified mass was 2 × 2 × 4 cm and the largest, 3 × 4 × 9 cm. Median follow-up was 4 years (range, 2-10 years). Six patients had excellent, 1 patient had good, and 4 patients had moderate outcomes; 7 of them were able to return to preinjury activities (Tegner score, 7-10). There were 2 cases of loss of skin sensation at the posterior femoral cutaneous nerve distribution, but neither patient described this as significantly interfering with any activity. All patients had symmetric side-to-side single-legged hop test and a 5 out of 5 on hamstring muscle strength at latest follow-up. Conclusion: Heterotopic ossifications that develop at the proximal hamstrings after eccentric load injuries can be associated with significant chronic disability. These cases can be effectively treated by surgical excision of the ossified masses and concomitant debridement with suture fixation of the proximal hamstring tendons to the ischium. Return to preinjury activities is expected in the majority of these cases, with low postoperative risks.